Pediatric perioperative adverse events requiring rapid response: a retrospective case–control study. Issue 7 (19th May 2016) - Schleelein, Laura E.; Vincent, Ariel M.; Jawad, Abbas F.; Pruitt, Eric Y.; Kreher, Genna D.; Rehman, Mohamed A.; Goebel, Theodora K.; Cohen, David E.; Cook‐Sather, Scott D.
Summary: Background: Perioperative pediatric adverse events have been challenging to study within and across institutions due to varying definitions, low event rates, and incomplete capture. Aim: The aim of this study was to determine perioperative adverse event prevalence and to evaluate associated case characteristics and potential contributing factors at an academic pediatric quaternary‐care center. Methods: At the Children's Hospital of Philadelphia (CHOP), perioperative adverse events requiring rapid response assistance are termed Anesthesia Now (AN!) events. They have been accurately captured and entered into a quality improvement database since 2010. Adverse events involving open heart and cardiac catheterization cases are managed separately and not included in this database. We conducted a retrospective case–control study utilizing Compurecord (Phillips Healthcare, Andover, MA, USA), EPIC (EPIC, Verona, WI, USA), and Chartmaxx (MedPlus, Mason, OH, USA) systems matching AN! event cases to noncardiac controls (1 : 2) based on surgical date. Results: From April 16, 2010 to September 25, 2012, we documented 213 AN! events in the noncardiac perioperative complex and remote sites at our main hospital. AN! prevalence was 0.0043 (1 : 234) with a 95% confidence interval (CI) (0.0037, 0.0049). Respiratory events, primarily laryngospasm, were most common followed by events of cardiovascular etiology. Median age was lower in the AN! group than in controls, 2.86 years (interquartile range 0.94, 10.1) vs 6.20 (2.85, 13.1), P < 0.0001. Odds ratios (with 95% CI) for age, 0.969 (0.941, 0.997); American Society of Anesthesiologists physical status, 1.67 (1.32, 2.12); multiple (≥2) services, 2.27 (1.13, 4.55); nonoperating room vs operating room location, 0.240 (0.133, 0.431); and attending anesthesiologist's experience, 0.976 (0.959, 0.992) were all significant. Conclusions: Decreased age, increased comorbidities, multiple (vs single) surgical services, operating room (vs nonoperating room) location, and decreased staff experience were associated with increased risk of AN! events, which were predominantly respiratory in origin. Abstract :